Effect of pH on the hinge region of influenza viral protein: a combined constant pH and well-tempered molecular dynamics study. (17th April 2018) - Pathak, Arup Kumar
Abstract: Despite the knowledge that the influenza protein, hemagglutinin, undergoes a large conformational change at low pH during the process of fusion with the host cell, its molecular mechanism remains elusive. The present constant pH molecular dynamics (CpHMD) study identifies the residues responsible for large conformational change in acidic condition. Based on the pKa calculations, it is predicted that His-106 is much more responsible for the large conformational change than any other residues in the hinge region of hemagglutinin protein. Potential of mean force profile from well-tempered meta-dynamics (WT-MtD) simulation is also generated along the folding pathway by considering radius of gyration ( R gyr ) as a collective variable (CV). It is very clear from the present WT-MtD study, that the initial bending starts at that hinge region, which may trigger other conformational changes. Both the protein–protein and protein–water HB time correlation functions are monitored along the folding pathway. The protein–protein (full or hinge region) HB time correlation functions are always found to be stronger than those of the protein–water time correlation functions. The dynamical balance between protein–protein and protein–water HB interactions favors the stabilization of the folded state.